2023
DOI: 10.1111/psyg.12998
|View full text |Cite
|
Sign up to set email alerts
|

Association between dependency and long sleep duration among elderly people: a community‐based study

Abstract: BackgroundLong sleep duration is a common sleep disorder among elderly people. Dependency increases with increasing age. This study aimed to assess the association between dependency and long sleep duration among elderly people.MethodsThis study is a population‐based cross‐sectional study. A total of 1152 participants aged ≥ 60 years were selected from 26 locations in China by a complex multistage sampling design. Data were collected through face‐to‐face interviews. Sleep duration was measured using the Pittsb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…On the other hand, sleep disorders are very common in the elderly population, with the prevalence increasing with age.2023 A survey found that more than 50 % of people over the age of 60 had insomnia, and the diagnosis of insomnia ranged from 12 % to 20 % [ 28 ]. In past studies, sleep disorders in older adults have been studied in a number of areas, ranging from sleep quality to various health-related effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sleep disorders are very common in the elderly population, with the prevalence increasing with age.2023 A survey found that more than 50 % of people over the age of 60 had insomnia, and the diagnosis of insomnia ranged from 12 % to 20 % [ 28 ]. In past studies, sleep disorders in older adults have been studied in a number of areas, ranging from sleep quality to various health-related effects.…”
Section: Introductionmentioning
confidence: 99%